Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1985
DOI: 10.1111/j.0022-3646.1985.00388.x
|View full text |Cite
|
Sign up to set email alerts
|

GROWTH AND BRANCHED HYDROCARBON PRODUCTION IN A STRAIN OF BOTRYOCOCCUS BRAUNII (CHLOROPHYTA)1

Abstract: A strain Botryococcus braunii Kütz. that produces high levels of branched hydrocarbons (botryococcenes) was grown under different environmental conditions to investigate the relationship between growth and hydrocarbon production. Carbon dioxide concentration had the most significant influence on growth; 0.3% CO2‐enriched cultures demonstrated a minimum mass doubling time of ca. 40 h, compared to ca. 6 days for ambient air cultures grown on the same buffered growth medium. The botryococcene fraction, which cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
33
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(42 citation statements)
references
References 24 publications
6
33
0
2
Order By: Relevance
“…The color of red light-grown cells changed to yellow during the 6 months that the cells were maintained under monochromatic illumination (data not shown). This change seemed to be due to an increase in the ratio of carotenes/chlorophyll content, based on the absorption spectrum of the 90% methanol extracts, as previously reported in the cyanobacteria Synechococcus and Prochlorococcus (Moore et al, 1995) and B. braunii during light-acclimating processes (Wolf et al, 1985). In contrast, the photosystem activity parameters such as Fv/Fm, qP, φII, and NPQ showed no difference among the blue, green, and red light-grown cells (Fig.…”
Section: Quantification Of 14 C-hydrocarbons By Thin-layer Chromatogrsupporting
confidence: 79%
See 1 more Smart Citation
“…The color of red light-grown cells changed to yellow during the 6 months that the cells were maintained under monochromatic illumination (data not shown). This change seemed to be due to an increase in the ratio of carotenes/chlorophyll content, based on the absorption spectrum of the 90% methanol extracts, as previously reported in the cyanobacteria Synechococcus and Prochlorococcus (Moore et al, 1995) and B. braunii during light-acclimating processes (Wolf et al, 1985). In contrast, the photosystem activity parameters such as Fv/Fm, qP, φII, and NPQ showed no difference among the blue, green, and red light-grown cells (Fig.…”
Section: Quantification Of 14 C-hydrocarbons By Thin-layer Chromatogrsupporting
confidence: 79%
“…An oil-producing green alga Botryococcus braunii is a promising renewable source of petroleum substitute, as it produces hydrocarbons by fixing atmospheric CO 2 photosynthetically (Banerjee et al, 2002;Casadevall et al, 1985;Largesu et al, 1980;Metzger and Largeau, 2005;Wolf et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that B. braunii Berkeley-strain grew at 1.2 g/l per week with continuous light (250 µE/m 2 /s) and 23-25°C 4) . A higher STS supply rate could cause an increase in the algal growth rate in the continuous system.…”
Section: )9)mentioning
confidence: 99%
“…Once produced, C 30 botryococcene is further metabolized by methylation at carbons 3, 7, 16, and 20 to produce C 31 , C 32 , C 33 , and C 34 botryococcenes (19,43,44), and even further methylated to C 36 and C 37 botryococcenes in some B race strains (22,45). In C 34 botryococcene-producing strains such as the Berkeley (Showa) strain, the majority (Ͼ99%) of the C 34 botryococcenes exist in the extracellular matrix whereas the intracellular oil comprises predominantly the lower carbon number botryococcenes (19,20). These botryococcenes are excreted to the extracellular matrix as they mature to C 34 botryococcene (19,20).…”
mentioning
confidence: 99%